2012
DOI: 10.1158/1055-9965.epi-11-0915
|View full text |Cite
|
Sign up to set email alerts
|

Workplace-Based Breast Cancer Screening Intervention in China

Abstract: Background: Breast cancer continues to be the primary cause of death among East and Southeast Asian women. Although China, the most populous country in the world, is experiencing unprecedented economic growth, its health care system has yet to benefit from the current economic prosperity. Indeed, studies have shown a consistent increase in breast cancer rates among Chinese women over the past two decades in the absence of breast cancer screening guidelines.Methods: The primary objective of this study was to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Pimps, venue owners, and bosses are uniquely positioned to facilitate sex worker engagement in HIV intervention activities. Past research has shown that this is an essential element to the success of health interventions in China (Ma et al, 2012; Wong, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Pimps, venue owners, and bosses are uniquely positioned to facilitate sex worker engagement in HIV intervention activities. Past research has shown that this is an essential element to the success of health interventions in China (Ma et al, 2012; Wong, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The study also followed up after 6 months to evaluate screening rates, and they found those in the intervention group were significantly more likely to have a mammogram within the 6 months post-education. [18] A program for breast cancer in Chinese American women found that a culturally tailored video for Chinese Americans in the Metro Washington, DC area increased screening intentions, knowledge, and understanding of Western medicine and decreased fears about breast cancer [19]. A recent education program targeted multiple Asian American ethnic groups including Chinese and Vietnamese, in which women who were previously non-adherent were more likely to schedule yearly mammograms after the breast cancer education program [20].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, mammography is the gold standard for early screening of breast cancer (Yip et al, 2008) because mammography has proven successful , Eun-Cheol Park 2,4 * in early detection and good prognosis for breast cancers across the range of ages and mutation status (Maurice et al, 2012). As such, some Asian countries, including Korea (Kim et al, 2011), Japan (Kikuchi et al, 2012), China (Huang et al, 2001;Ma et al, 2012), and Taiwan (Huang et al, 2001;Leong et al, 2010), as well as many Western countries, including the US (White et al, 1990;USPSTF, 2009), Canada (Tonelli et al, 2011), the UK (Parkin et al, 2005;Evans et al, 2012), Norway (Lynge et al, 2011;Hofvind et al, 2012;Olsen et al, 2013), and The Netherlands (de Koning et al, 1995;Fracheboud et al, 1998), are implementing mammography for breast cancer screening and they expect lower mortality as well as cost-effectiveness, but the cost-effectiveness was unclear (Kikuchi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%